TREN PENGGUNAAN MEDIA SOSIAL SELAMA PANDEMI DI INDONESIA - Machyudin Agung Harahap; Susri Adeni (Professional: Jurnal Komunikasi dan Administrasi Publik, 2020)
The internet users in Indonesia show a significant numbers and they use it mostly for social media. This research is conducted to explore the trend of social media usage during the pandemic in Indonesia. It is in order to have a decription in how internet used during the pandemic. The research method is done by study literature from many kinds of articles, scholarly journals, books, manuscripts and others sources related to the theme of this article. The result is social media is used by housewive to generate their family income during the pandemic. Interestingly, during the pandemic, the housewive become actively used social media to do online business such as food and beverage and other things.